(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Inconel 718 with exceptional characteristics is well known as a difficult-to-cut material especially during high-speed machining process. High cutting temperature further damaged the tool which results in low tool life. To overcome this matter, optimization on cutting parameters needed to be conducted in order to achieve longer tool life and desired cutting finish. Sets of optimized parameters consists of different cutting speed and feed rate were listed out through Research Surface Method (RSM) software which the effects and the output values were observed through high-speed end milling work on a 100 x 100 x 150 mm Inconel 718 block. The lowest cutting force and surface roughness at 776.04 N and 0.195 µm were recorded at the lowest parameter combination, while the highest results of 1,322.89 N and 0.478 µm were obtained from the highest parameter combination. Higher cutting parameter further deteriorate the cutting tool due to high heat and drastic reduction in tool life was observed, from 32 minutes of cutting process to only 2 minutes and 40 seconds. The results were further investigated through optimization work and cutting speed is the dominant factor that affected the results. The final model suggested that by using uncoated carbide tools, the lowest cutting speed and feed rate of 50 m/min and 0.05 mm/tooth can be implemented to obtain the desired cutting responses.